Lithological influence on Li isotope fractionation during silicate weathering - Chris T.L. Cheung; Brian Beaty; Kohen W. Bauer; Cody L. Colleps; Dan Asael; Sean A. Crowe; Noah J. Planavsky; Paul S. Savage; N. Ryan McKenzie (Geochimica et Cosmochimica Acta, 2026)

Sedimentary Mo isotope variability reflects climate-driven water column oxygenation changes in ferruginous Lake Towuti, Indonesia over the last ∼30 ka BP - Adrianus Damanik; Martin Wille; Qasid Ahmad; Sean A. Crowe; Kohen W. Bauer; Martin Grosjean; Sri Yudawati Cahyarini; Satria Bijaksana; James M. Russell; Hendrik Vogel (Quaternary Science Reviews, 2025)

Stratification stability of tropical lakes and their sensitivity to climate - Tongyao Pu; G. Douglas Haffner; Sean A. Crowe; Sergei Katsev (Limnology and Oceanography, 2025)
Tropical lakes experience less thermal convection than temperate lakes and can be stably stratified by temperature gradients alone. Deep tropical lakes are often presumed meromictic, but conditions for sustained meromixis are poorly constrained. Here, we investigate the stratification stability of a deep (200 m) tropical Lake Towuti (Indonesia) and analyze its sensitivity to meteorological and climatic parameters using exploratory hydrodynamic simulations. The inferred effects on water chemistry are further evaluated with a reactive‐transport biogeochemical model. In contrast to the previous assumption of meromixis, our results suggest that in 2008 Lake Towuti experienced mixing over most of its water column, with the attendant weak oxygenation of the previously anoxic lower strata. The lake likely remained stratified afterwards, but the chemical distributions measured after the episode, particularly during the International Continental Scientific Drilling Program in 2015, were out of steady state, and may be still evolving in time. We find the thermal stratification to be most sensitive to average air temperatures and wind speeds and predict further stabilization of the lake by climate change. We also describe a negative feedback mechanism that can stabilize oligomictic tropical lakes for a number of years after the episodes of mixing and cooling, and infer that such episodes should be significantly less frequent in deeper lakes.

Microbial community respiration kinetics and their dynamics in coastal seawater - Henry L.S. Cheung; Rachel L. Simister; Christelle Not; Sean A. Crowe (Science of The Total Environment, 2024)

Low Mo mobility during the laterization of ultramafic bedrock: Evidence from the East Sulawesi Ophiolite, Indonesia - Adrianus Damanik; Martin Wille; Qasid Ahmad; Sukalpa Chatterjee; Sean A. Crowe; Kohen W. Bauer; Martin Grosjean; Sri Yudawati Cahyarini; Satria Bijaksana; James M. Russell; Hendrik Vogel (Chemical Geology, 2024)

Salinity, mineralogy, porosity, and hydrodynamics as drivers of carbon burial in urban mangroves from a megacity - Laetitia Allais; Benoit Thibodeau; Nicole S. Khan; Sean A. Crowe; Stefano Cannicci; Christelle Not (Science of The Total Environment, 2024)

Preservation of organic C and N isotope signatures from water column to sediments in the anoxic and ferruginous Pavin lake - Vincent Busigny; Oanez Lebeau; Didier Jézéquel; Carine Chaduteau; Sean Crowe; Magali Ader (Chemical Geology, 2024)

Earth’s surface oxygenation and the rise of eukaryotic life: Relationships to the Lomagundi positive carbon isotope excursion revisited - Mojtaba Fakhraee; Lidya G. Tarhan; Christopher T. Reinhard; Sean A. Crowe; Timothy W. Lyons; Noah J. Planavsky (Earth-Science Reviews, 2023)

Manganese oxides, Earth surface oxygenation, and the rise of oxygenic photosynthesis - Leslie J. Robbins; Mojtaba Fakhraee; Albertus J.B. Smith; Brendan A. Bishop; Elizabeth D. Swanner; Caroline L. Peacock; Chang-Le Wang; Noah J. Planavsky; Christopher T. Reinhard; Sean A. Crowe; Timothy W. Lyons (Earth-Science Reviews, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Functional redundancy imparts process stability to acidic Fe( II )‐oxidizing microbial reactors - Diana Ayala‐Muñoz; Rachel L. Simister; Sean A. Crowe; Jennifer L. Macalady; William D. Burgos (Environmental Microbiology, 2021)
Summary In previous work, lab‐scale reactors designed to study microbial Fe(II) oxidation rates at low pH were found to have stable rates under a wide range of pH and Fe(II) concentrations. Since the stirred reactor environment eliminates many of the temporal and spatial variations that promote high diversity among microbial populations in nature, we were surprised that the reactors supported multiple taxa presumed to be autotrophic Fe(II) oxidizers based on their phylogeny. Metagenomic analyses of the reactor communities revealed differences in the metabolic potential of these taxa with respect to Fe(II) oxidation and carbon fixation pathways, acquisition of potentially growth‐limiting substrates and the ability to form biofilms. Our findings support the hypothesis that the long‐term co‐existence of multiple autotrophic Fe(II)‐oxidizing populations in the reactors are due to distinct metabolic potential that supports differential growth in response to limiting resources such as nitrogen, phosphorus and oxygen. Our data also highlight the role of biofilms in creating spatially distinct geochemical niches that enable the co‐existence of multiple taxa that occupy the same apparent metabolic niche when the system is viewed in bulk. The distribution of key metabolic functions across different co‐existing taxa supported functional redundancy and imparted process stability to these reactors.

Sampling and Processing Methods Impact Microbial Community Structure and Potential Activity in a Seasonally Anoxic Fjord: Saanich Inlet, British Columbia - Mónica Torres-Beltrán; Andreas Mueller; Melanie Scofield; Maria G. Pachiadaki; Craig Taylor; Kateryna Tyshchenko; Céline Michiels; Phyllis Lam; Osvaldo Ulloa; Klaus Jürgens; Jung-Ho Hyun; Virginia P. Edgcomb; et al. (Frontiers in Marine Science, 2019)

Rates and Pathways of N2 Production in a Persistently Anoxic Fjord: Saanich Inlet, British Columbia - Céline C. Michiels; Julia A. Huggins; Karina E. Giesbrecht; Jenifer S. Spence; Rachel L. Simister; Diana E. Varela; Steven J. Hallam; Sean A. Crowe (Frontiers in Marine Science, 2019)

Metabolic potential of microbial communities from ferruginous sediments - Aurèle Vuillemin; Fabian Horn; André Friese; Matthias Winkel; Mashal Alawi; Dirk Wagner; Cynthia Henny; William D. Orsi; Sean A. Crowe; Jens Kallmeyer (Environmental Microbiology, 2018)
Summary Ferruginous (Fe‐rich, SO 4 ‐poor) conditions are generally restricted to freshwater sediments on Earth today, but were likely widespread during the Archean and Proterozoic Eons. Lake Towuti, Indonesia, is a large ferruginous lake that likely hosts geochemical processes analogous to those that operated in the ferruginous Archean ocean. The metabolic potential of microbial communities and related biogeochemical cycling under such conditions remain largely unknown. We combined geochemical measurements (pore water chemistry, sulfate reduction rates) with metagenomics to link metabolic potential with geochemical processes in the upper 50 cm of sediment. Microbial diversity and quantities of genes for dissimilatory sulfate reduction ( dsrAB ) and methanogenesis ( mcrA ) decrease with increasing depth, as do rates of potential sulfate reduction. The presence of taxa affiliated with known iron‐ and sulfate‐reducers implies potential use of ferric iron and sulfate as electron acceptors. Pore‐water concentrations of acetate imply active production through fermentation. Fermentation likely provides substrates for respiration with iron and sulfate as electron donors and for methanogens that were detected throughout the core. The presence of ANME‐1 16S and mcrA genes suggests potential for anaerobic methane oxidation. Overall our data suggest that microbial community metabolism in anoxic ferruginous sediments support coupled Fe, S and C biogeochemical cycling.

Denitrification, anaerobic ammonium oxidation, and dissimilatory nitrate reduction to ammonium in an East African Great Lake (Lake Kivu) - Fleur A. E. Roland; François Darchambeau; Alberto V. Borges; Cédric Morana; Loreto De Brabandere; Bo Thamdrup; Sean A. Crowe (Limnology and Oceanography, 2018)
We investigated anaerobic nitrogen (N) cycling in the water column of Lake Kivu, a deep meromictic tropical lake in East Africa. Data were collected at one station in the Northern Basin and one in the Southern Basin, during two sampling campaigns (June 2011—dry season, and February 2012—rainy season). Short‐term incubations of sulfide‐free water with 15 N‐labeled substrates revealed high potential denitrification and dissimilatory nitrate reduction to ammonium (DNRA) rates (up to 350 and 36 nmol N produced L −1 h −1 , respectively), while anaerobic ammonium oxidation (anammox) was lower (up to 3.3 nmol N produced L −1 h −1 ). However, anammox rates were 15 nmol N produced L −1 h −1 when 15 was added at depths where concentrations were very low ( −1 ). With the addition of 5 μmol L −1 of 15 and 10 μmol L −1 of H 2 S, denitrification and anammox were stimulated in the Northern Basin, while the increase of DNRA rates was less notable. In the Southern Basin, the addition of H 2 S decreased denitrification rates, probably because of competition with DNRA, which increased, while no effect was observed on anammox. This study puts into evidence the co‐occurrence of denitrification, anammox and DNRA, for the first time in a great tropical lake, and underlines the spatial heterogeneity of these processes. Contrary to numerous reports in literature, we show that anammox can significantly occur in presence of H 2 S, suggesting that the contribution of anammox in the N cycle may be underestimated.

Chemoautotrophy and anoxygenic photosynthesis within the water column of a large meromictic tropical lake (Lake Kivu, East Africa) - Cédric Morana; Fleur A. E. Roland; Sean A. Crowe; Marc Llirós; Alberto V. Borges; François Darchambeau; Steven Bouillon (Limnology and Oceanography, 2016)
We quantified chemoautotrophic and anoxygenic photosynthetic microbial production in the water column of Lake Kivu, a permanently stratified tropical lake situated amidst volcanic activity, and aimed to identify the microorganisms involved in these processes through the analysis of their phospholipid fatty acid (PLFA) content and stable isotope ( 13 C) labelling of PLFA in a set of incubation experiments. Data demonstrate the existence of a biogeochemically active chemoautotrophic bacterial community in the redoxcline of Lake Kivu (50–70 m). PLFA data indicate that the bacterial communities are structured vertically in the water column, with a large dissimilarity between the oxic and anoxic waters. Maximum volumetric dark CO 2 fixation rates measured in Lake Kivu were in the same range as values reported from H 2 S‐rich marine redoxclines, such as the Black and Baltic Seas, and the Cariaco Basin. Similarly, maximal chemoautotrophic activities in Lake Kivu were observed in sulfidic waters, just below the oxycline. Anoxygenic photosynthetic production was never observed in the main basin of Lake Kivu. However, anoxygenic phototrophs largely dominated CO 2 fixation in the illuminated redoxcline of Kabuno Bay, a shallower ferruginous sub‐basin. Overall, this study supports the idea that chemoautotrophs and/or anoxygenic photoautotrophs might play an important role in the flow of carbon and energy in permanently stratified tropical ecosystems. In Lake Kivu, these processes significantly contribute to organic matter biosynthesis and exert an indirect control on oxygenic photoautotrophs by shortcircuiting the vertical transport of nutrients to the illuminated and oxygenated surface waters.

Heterotrophic bacteria from an extremely phosphate‐poor lake have conditionally reduced phosphorus demand and utilize diverse sources of phosphorus - Mengyin Yao; Felix J. Elling; CarriAyne Jones; Sulung Nomosatryo; Christopher P. Long; Sean A. Crowe; Maciek R. Antoniewicz; Kai‐Uwe Hinrichs; Julia A. Maresca (Environmental Microbiology, 2016)
Summary Heterotrophic P roteobacteria and A ctinobacteria were isolated from L ake M atano, I ndonesia, a stratified, ferruginous (iron‐rich), ultra‐oligotrophic lake with phosphate concentrations below 50 nM. Here, we describe the growth of eight strains of heterotrophic bacteria on a variety of soluble and insoluble sources of phosphorus. When transferred to medium without added phosphorus ( P ), the isolates grow slowly, their RNA content falls to as low as 1% of cellular dry weight, and 86–100% of the membrane lipids are replaced with amino‐ or glycolipids. Similar changes in lipid composition have been observed in marine photoautotrophs and soil heterotrophs, and similar flexibility in phosphorus sources has been demonstrated in marine and soil‐dwelling heterotrophs. Our results demonstrate that heterotrophs isolated from this unusual environment alter their macromolecular composition, which allows the organisms to grow efficiently even in their extremely phosphorus‐limited environment.

Carbon mineralization and oxygen dynamics in sediments with deep oxygen penetration, Lake Superior - Jiying Li; Sean A. Crowe; David Miklesh; Matthew Kistner; Donald E. Canfield; Sergei Katsev (Limnology and Oceanography, 2012)
To understand carbon and oxygen dynamics in sediments with deep oxygen penetration, we investigated eight locations (160–318‐m depth) throughout Lake Superior. Despite the 2–4 weight percent organic carbon content, oxygen penetrated into the sediment by 3.5 to > 12 cm at all locations. Such deep penetration is explained by low sedimentation rates (0.01–0.04 cm yr −1 ), high solubility of oxygen in freshwater, and a shallow (~ 2 cm) bioturbation zone. In response mainly to oxygen variations in the bottom waters, the sediment oxygen penetration varied seasonally by as much as several centimeters, suggesting that temporal variability in deeply oxygenated sediments may be greater than previously acknowledged. The oxygen uptake rates (4.4–7.7 mmol m −2 d −1 , average 6.1 mmol m −2 d −1 ) and carbon mineralization efficiency (~ 90% of deposited carbon) were similar to those in marine hemipelagic and pelagic sediments of comparable sedimentation rates. The reactivity of organic carbon was found to decrease with age similarly to the power‐law documented in marine environments. The burial flux of carbon into the deep sediment (0.7 mmol m −2 d −1 ) was 2.5% of the previously estimated primary production. Maximum volume‐specific carbon degradation rates were 0.3–1.5 µmol cm −3 d −1 ; bioturbation coefficient near the sediment surface was 3–8 cm 2 yr −1 . These results indicate that carbon cycling in large freshwater systems conforms to many of the same trends as in marine systems.

Mixing and its effects on biogeochemistry in the persistently stratified, deep, tropical Lake Matano, Indonesia - Sergei Katsev; Sean A. Crowe; Alfonso Mucci; Bjørn Sundby; Sulung Nomosatryo; G. Douglas Haffner; David A. Fowle (Limnology and Oceanography, 2010)
In the > 590‐m deep, tropical Lake Matano (Indonesia), stratification is characterized by weak thermal gradients ( K z ) cannot be estimated by conventional methods that rely on time derivatives of temperature distributions. We use and compare several alternative methods: one‐dimensional k ‐ε modeling, three‐dimensional hydrodynamic modeling, correlation with the size of Thorpe instabilities, and correlation with the stability frequency. In the thermocline region, at 100‐m depth, the K z is ~ 5 × 10 −6 m 2 s −1 , but, below 300 m, the small density gradient results in large (20 m) vertical eddies and high mixing rates ( K z ~ 10 −2 m 2 s −1 ). The estimated timescale of water renewal in the monimolimnion is several hundred years. Intense evaporation depletes the surface mixed layer of 16 O and 1 H isotopes, making it isotopically heavier. The lake waters become progressively isotopically lighter with depth, and the isotopic composition in the deep waters is close to those of the ground and tributary waters. The vertical distribution of K z is used in a biogeochemical reaction‐transport model. We show that, outside of a narrow thermocline region, the vertical distributions of dissolved oxygen, iron, methane, and phosphorus are shaped by vertical variations in transport rates, rather than by sources or sinks.

The biogeochemistry of tropical lakes: A case study from Lake Matano, Indonesia - Sean A. Crowe; Andrew H. O’Neill; Sergei Katsev; Peter Hehanussa; G. Douglas Haffner; Bjørn Sundby; Alfonso Mucci; David A. Fowle (Limnology and Oceanography, 2008)
We examined the chemical composition of the water column of Lake Matano, Sulawesi Island, Indonesia, to document how the high abundances of Fe (hydr)oxides in tropical soils and minimal seasonal temperature variability affect biogeochemical cycling in lakes. Lake Matano exhibits weak thermal stratification, yet a persistent pycnocline separates an oxic epilimnion from anoxic meta‐ and hypolimnions. The concentration of soluble P in the epilimnetic waters is very low and can be attributed to scavenging by Fe (hydr)oxides. Chromium concentrations in the epilimnion are high (up to 180 nmol L −1 ), but below U.S. Environmental Protection Agency guidelines for aquatic ecosystems. The concentration of chromium decreases sharply across the oxic‐anoxic boundary, revealing that the hypolimnion is a sink for Cr. Flux calculations using a one‐dimensional transportreaction model for the water column fail to satisfy mass balance requirements and indicate that sediment transport and diagenesis play an important role in the exchange of Fe, Mn, P, and Cr between the epilimnion and hypolimnion. Exchange of water between the epilimnion and hypolimnion is slow and on a time scale similar to temperate meromictic lakes. This limits recycling of P and N to the epilimnion and removal of Cr to the hypolimnion, both of which likely restrict primary production in the epilimnion. Owing to the slow exchange, steep concentration gradients in Fe and Mn species develop in the metalimnion. These concentration gradients are conducive to the proliferation of chemoautotrophic and anoxygenic phototrophic microbial communities, which may contribute a significant fraction to the total primary production in the lake.

Genetic and structural determinants of virus neutralizing antibodies - James E. Crowe; Rahaman O. Suara; Sean Brock; Nicole Kallewaard; Frances House; Jörn-Hendrick Weitkamp (Immunologic Research, 2001)